Glucosinolates from Host Plants Influence Growth of the Parasitic Plant Cuscuta gronovii and Its Susceptibility to Aphid Feeding . Issue 1 (1st August 2016) - Smith, Jason D.; Woldemariam, Melkamu G.; Mescher, Mark C.; Jander, Georg; De Moraes, Consuelo M.
Abstract : Dodder vines (Cuscuta gronovii) parasitizing Arabidopsis thaliana take up glucosinolate toxins that reduce parasite growth and modulate resistance to aphid herbivores. Abstract: Parasitic plants acquire diverse secondary metabolites from their hosts, including defense compounds that target insect herbivores. However, the ecological implications of this phenomenon, including the potential enhancement of parasite defenses, remain largely unexplored. We studied the translocation of glucosinolates from the brassicaceous host plant Arabidopsis ( Arabidopsis thaliana ) into parasitic dodder vines (Convolvulaceae; Cuscuta gronovii ) and its effects on the parasite itself and on dodder-aphid interactions. Aliphatic and indole glucosinolates reached concentrations in parasite tissues higher than those observed in corresponding host tissues. Dodder growth was enhanced on cyp79B2 cyp79B3 hosts (without indole glucosinolates) but inhibited on atr1D hosts (with elevated indole glucosinolates) relative to wild-type hosts, which responded to parasitism with localized elevation of indole and aliphatic glucosinolates. These findings implicate indole glucosinolates in defense against parasitic plants. Rates of settling and survival on dodder vines by pea aphids ( Acyrthosiphon pisum ) were reduced significantly when dodder parasitized glucosinolate-producing hosts (wild type and atr1D ) compared with glucosinolate-free hosts ( cyp79B2 cyp79B3 myb28 myb29 ). However, settling and survival of green peach aphids ( Myzus persicae ) were not affected. M. persicae population growth was actually reduced on dodder parasitizing glucosinolate-free hosts compared with wild-type or atr1D hosts, even though stems of the former contain less glucosinolates and more amino acids. Strikingly, this effect was reversed when the aphids fed directly upon Arabidopsis, which indicates an interactive effect of parasite and host genotype on M. persicae that stems from host effects on dodder. Thus, our findings indicate that glucosinolates may have both direct and indirect effects on dodder-feeding herbivores.